Amylose in starch: towards an understanding of biosynthesis, structure and function - Seung, David (The New phytologist, 2020)
Starch granules are composed of two distinct glucose polymers – amylose and amylopectin. Amylose constitutes 5–35% of most natural starches and has a major influence over starch properties in foods. Its synthesis and storage occurs within the semicrystalline amylopectin matrix of starch granules, this poses a great challenge for biochemical and structural analyses. However, the last two decades have seen vast progress in understanding amylose synthesis, including new insights into the action of GRANULE BOUND STARCH SYNTHASE (GBSS), the major glucosyltransferase that synthesises amylose, and the discovery of PROTEIN TARGETING TO STARCH1 (PTST1) that targets GBSS to starch granules. Advances in analytical techniques have resolved the fine structure of amylose, raising new questions on how structure is determined during biosynthesis. Furthermore, the discovery of wild plants that do not produce amylose revives a long-standing question of why starch granules contain amylose, rather than amylopectin alone. Overall, these findings contribute towards a full understanding of amylose biosynthesis, structure and function that will be essential for future approaches to improve starch quality in crops.